‘12 tips for teaching environmental sustainability to health professionals’ - Schwerdtle, Patricia; Maxwell, Janie; Horton, Graeme; Bonnamy, James (Medical teacher, 2020)
As recognition of the health impacts of climate change and other environmental challenges increases, so too does the need for health care professionals to practice healthcare sustainably. Environmental sustainability in healthcare extends beyond our traditional understanding of environmental health, which is often limited to environmental hazards and disease. Health services, professional organizations, and training institutions are increasingly forming climate and sustainability position statements and policies accordingly. To prepare future health professionals for global environmental change, environmental sustainability must be meaningfully integrated into health curricula. Aim: To provide educators with 12 tips for integrating environmental sustainability into health professional education.